POLICE SELF DEFENSE TRAINING AND STRESS AS A SHORT TERM DIDACTIC RESOURCE (Fiep Bulletin - online, 2017)
Stress results to be the conditioning factor of our behavior. When faced to a situation of imminent risk, it activatesunconscious systems that can cause automatic reactions, those reactions will be conditioned by learning and previous experience.That is why it is fundamental that, during the process of teaching-learning, experience that serves as unconscious response whenneeded to solve a violent situation that necessarily puts us in defensive stance, is created.The “Cesar” System in self defense training suggests combining the techniques and own strategies of this activity andexpose stress by the creation and representation of violent scenes, trying to “cheat” the nervous system and so creating theconditioned reflex necessary to trigger the expected reaction in front of a compromising situation, allowing to have control over theresponse protecting the lives of everyone involved.Over the basis of an action investigation, many teaching resources were used for training as well as the observation thattook place in flashing periods between 1993 and 2015. According to the information gathered during the years 2014/15, we can sayensure the efficiency of the “Cesar” System as long as it is given in the detailed conditions, especially with the participation of thephysical education and martial arts professors and the participation of the specialist in psychology as part of the interdisciplinaryteam.